Language Learning Technologies to Support Indonesian EFL Students' Writing Skills: A Literature Review - Nurfadillah; Achmad Nurcholis, Ivan (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2025)
The utilization of technology in educational settings, particularly in the context of English as a Foreign Language (EFL) instruction, exerts a substantial influence on students' writing abilities. This research study undertakes a comprehensive analysis of the impact of Technology Assisted Language Learning (TALL) on the writing proficiency of EFL students in Indonesia. The study is informed by a systematic review of diverse studies conducted over the past decade. The primary focus of this analysis is to examine how technological tools enhance students' writing abilities. The findings indicate that TALL enhances writing proficiency through interactive learning, prompt feedback, and collaborative activities. However, the study also identifies challenges, including a lack of teacher preparation and limited access to technology. The study's conclusion emphasizes that while TALL offers numerous benefits, addressing these issues is crucial to maximize its efficacy. Recommendations for optimizing TALL include increased investment in technology infrastructure, professional development for educators, and integration of TALL in the curriculum.